al-Taswîq Muta'addid al-Mustawayât al-Mustawayât fî Daw al-Maqâsîd al-Shar'iyyah al-Khâssah bi al-Mâl - Rais Abdullah; Rabiatul Adawiyah; Abdul Gafur (Sultang Agung Islamic University, 2021)
Multilevel marketing is a new case that is not found in the legal explanation of the Al-qur’ān or in the sunnah; to determine the law, the moslem scholars have “ijtihād” by using various approaches, both economic approaches and fiqh approaches. Because of the different points of view they use, the legal provisions produced vary; some forbid, and others allow. This study seeks to highlight multilevel marketing from the perspective of Maqāṣid syari’a relating to property, this study is carried out using qualitative analytical descriptive methods and is based on literature. The significance of this study is because it bases its discussion on maqāṣid syari’a, which is a discipline that reveals the wisdom, and the ultimate goal of a rule set by God for humans. The results of the study confirm that multilevel marketing in practice violates the principles of maqāṣid syari’a relating to property; therefore, this study strengthens the opinion that prohibits the practice of multilevel marketing in economic Activities